The Status of Clinical Teaching from Viewpoint of Faculty Members and Students in Guilan University of Medical Sciences - Arsalan Salari; Ideh Dadgaran; Leila Rouhi Balasi; Fatemeh Moaddab; Hossein Khoshrang; Azam Nourisaeed (Tabriz University of Medical Sciences, 2016)
Background: One of the main tasks of the faculty of medical sciences is clinical training. Given the importance of clinical teaching for medical students, the study aim was to determine the clinical teaching status from the perspective of students and faculty members. Methods: The population of this cross-sectional study was all medical interns and final-year students of nursing and midwifery and faculty members of Guilan University of Medical Sciences in the 2015. The sampling was conducted by census method after obtaining the consent of the participants. The scale was a questionnaire consisting of 4 parts, including demographic data,phrases related to clinical teaching principles by faculty members, phrases related to the use of material and educational media by clinical faculty members and phrases related to educational activities by clinical faculty members. Data analysis was done by descriptive and inferential statistics (Mann-Whitney U test). Results: Based on the results, the mean score of clinical teaching status from the perspective of the faculty members was 62.88 ± 5.76 out of a score of 66, and the mean score was 52.11 ± 1.1 from the students' perspective. Mann-Whitney U test results also showed a significant difference between faculty members' and students' perspective scores about clinical teaching status(P < 0.0001). Conclusion: According to the findings of this study, to improve the quality of clinical education,implementation strategies will be necessary. One of the most important parts of teaching in the field of medical science is clinical education as it is the first real experience students have with their future work environment and it has a significant impact on their occupational success.